Framing of Educational News during COVID-19: A Comparative Analysis of Pakistani News Channels - Sana Rauf; Nazia Rehman; Durr-e-Shehwar, (ASIAN Journal of International Peace & Security (AJIPS), 2022)
The COVID-19 pandemic swept the world, causing a chain of crises that affected every industry and individual. Education was among the areas which were affected most during COVID 19. In Pakistan, schools, colleges and universities were shut and media was the only source to effectively portray the educational issues of young population. This study was designed to examine the news coverage of educational issues during the COVID-19 period in Pakistan by the leading news channels, Geo News and ARY News. Quantitative content analysis was carried out for 133 educational news broadcasted by both of the channels, between March 23rd, 2020, to March 30th, 2021 during prime time. The educational news stories were coded by generic and issue-specific frames, tone, slant, and frequency. The analysis discovered substantial variations in the usage of evaluative tones, frames and extent of coverage given to educational issues during the COVID-19 Pandemic. The study also found out lack of coverage given to educational issues in the country as both channels gave only 12% coverage altogether.